2008
DOI: 10.1002/mnfr.200700481
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of tyrosinase inhibitors from Artocarpus heterophyllus and use of its extract as antibrowning agent

Abstract: A new furanoflavone, 7-(2,4-dihydroxyphenyl)-4-hydroxy-2-(2-hydroxy propan-2-yl)-2, 3-dihydrofuro(3, 2-g)chromen-5-one (artocarpfuranol, 1), together with 14 known compounds, dihydromorin (2), steppogenin (3), norartocarpetin (4), artocarpanone (5), artocarpesin (6), artocarpin (7), cycloartocarpin (8), cycloartocarpesin (9), artocarpetin (10), brosimone I (11), cudraflavone B (12), carpachromene (13), isoartocarpesin (14), and cyanomaclurin (15) were isolated from the wood of Artocarpus heterophyllus. Their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 34 publications
1
78
0
Order By: Relevance
“…The inhibition of tyroisnase activity can be accomplished by several mechanism, as follows: First, several polyphenols are accepted as substrates by tyrosinase. It is serves by the same slow-binding and competitive inhibition mode against mushroom tyrosinase (25,26). Second, a long-chain fatty acid inhibited monophenolase and diphenolase of mushroom tyrosinase (27,28).…”
Section: Fatty Acid Extractionmentioning
confidence: 97%
“…The inhibition of tyroisnase activity can be accomplished by several mechanism, as follows: First, several polyphenols are accepted as substrates by tyrosinase. It is serves by the same slow-binding and competitive inhibition mode against mushroom tyrosinase (25,26). Second, a long-chain fatty acid inhibited monophenolase and diphenolase of mushroom tyrosinase (27,28).…”
Section: Fatty Acid Extractionmentioning
confidence: 97%
“…In addition, it also possessed some antiplatelet activity (Lin et al, 1996). Cyanomaclurin (4) inhibited mushroom tyrosinase activity with an IC 50 value of 68.7 mM (Zheng et al, 2008). Thus, some of these bioactive flavonoids may be recommended for use as markers for standardization of the extracts of A. heterophyllus heartwoods in a quality control process that might be involved in developing preparations suitable for use as herbal medicines.…”
Section: Resultsmentioning
confidence: 99%
“…The spectral data were compared with the data in the literature (Likhitwitayawuid et al, 2000;Wang et al, 2004;Zheng et al, 2008).…”
Section: Identification Of the Purified Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few pharmacological activities were reported for pachycarin A, 3',4'-dimethoxy[2",3": 7,8]furanoflavone and isoderricin A, even though they have been known for years. However, previous researchers showed that furanoflavones can be used as antibrowning agents [30] and can also have antioxidant and radical quenching activities [31]. Pyranoflavones have antimycobacterial [32] and cytotoxic activities [33], and so on.…”
Section: Identification Of Fc and Mpmentioning
confidence: 99%